Why change does (not) happen: Understanding and overcoming status quo biases in climate change mitigation - Simon Rabaa; Sylvie Geisendorf; Robert Wilken (Zeitschrift für Umweltpolitik und Umweltrecht, 2022)
In its recent special reports, the Intergovernmental Panel on Climate Change (IPCC) emphasizes the importance of behavior and lifestyle changes in mitigating climate change and calls for them to be better researched. Yet to date, climate-related behavior has been largely neglected or simplified as rational decision making in the climate debate, both in analyzing and predicting the situation and in the design of policy solutions. This paper aims to fill this gap by presenting a specific kind of cognitive biases as irrational reasons for not taking enough climate action. Specifically, it deals with effects that cause people not to deviate from a given situation, so-called status quo biases. These biases have been described under many different names in behavioral economics and psychology, but so far, a systematic investigation of their influence on climate-relevant behavior is lacking. Consequently, we develop a categorization of 20 such mechanisms from different domains that can be grouped into five clusters within which they have a similar influence on climate-relevant behavior. In this way, we first aim to create a common understanding of the phenomenon and structure the discussion about it. Second, this systematic structure is used to propose policy options for dealing with the aforementioned biases. Third and most interestingly, we show how some of the biases can work both ways, i.e., can also be flipped into the positive to create and support a new climate-friendly status quo. We thus highlight new policy opportunities beyond material incentives to encourage climate-friendly behavior.
Keywords: 330; Climate change mitigation; Status quo bias; Cognitive biases; Behavioral economics; Psychology; Climate policy